SOSIALISASI TERHADAP ANAK-ANAK MENGENAI MANFAAT MEDIA SOSIAL YANG BIJAK DAN AMAN BAGI PEMBELAJARAN DI SDK NANAEKLOT - Ermelinda Siquiera; Christian Melania Mali Dasi; Stefanus Don Rade (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
Social media is a digital platform that allows users to interact with others through digital content. Social media has become an integral part of everyone's life, allowing them to follow news, find and follow people, and share information with others. However, the use of social media also has some risks, such as increasing addiction, opening up opportunities for negative behavior, and increasing privacy risks. Therefore, it is important to use social media wisely and understand the potential risks associated with it. This Social Service Program at SDK Nanaeklot aims to increase students' understanding of using social media wisely and responsibly. This activity will involve training and discussion sessions on the benefits and risks of using social media, how to choose the right social media platform, how to create a safe profile, and how to increase digital intelligence